Assessment of Intrafraction Motion of the Urinary Bladder Using Magnetic Resonance Imaging (cineMRI). Issue 2 (February 2020) - Wilson, C.; Moseshvili, E.; Tacey, M.; Quin, I.; Lawrentschuk, N.; Bolton, D.; Joon, D.L.; Chao, M.; Dunshea, T.; Kron, T.; Foroudi, F.
Abstract: Aim: To assess the intrafraction motion of the urinary bladder and delineate the appropriate margin size for radiotherapy planning, for both the full and empty bladder. Materials and methods: This was a single-site, single-arm study of 20 patients planned to undergo radical cystectomy for histologically confirmed muscle-invasive bladder cancer. Patients underwent magnetic resonance imaging (cineMRI) of the entire pelvis using a 3-Tesla system, prior to cystectomy. Patients first underwent a cineMRI with a full bladder, then voided and underwent a second MRI with an empty bladder. All MRI sequences were acquired over 18 min. We assessed the differences in bladder filling and subsequent bladder wall displacement, between the empty and full bladder, during a time period consistent with radiotherapy treatment delivery. Results: Twenty patients underwent cineMRI of the entire pelvis. The maximum mean directional displacements of the bladder walls over the 18 min duration of the scan for the empty bladders were 9.8 mm superiorly, 1.1 mm inferiorly, 2.39 mm anteriorly, 3.73 mm posteriorly, 2.74 mm to the left and 2.48 mm to the right. The maximal mean displacements for the full bladders were 9.2 mm superiorly, 1.1 mm inferiorly, 2.28 mm anteriorly, 1.08 mm posteriorly, 1.85 mm to the left and 1.73 mm to the right. Statistically significant differences were seen in the posterior, left and right displacements but were quantitatively small. Conclusions: Intrafractional motion secondary to bladder filling showed minimal variation between the full and empty bladder. Similar clinical target volume to planning target volume margins can be applied for the delivery of radiotherapy for a full and empty bladder. Highlights: No differences in volume change between full and empty bladders. Minimal differences in directional displacement between full and empty bladders. Mean bladder wall displacement <10 mm in all directions over 18 min. Similar planning target volumes required for whole and partial bladder radiotherapy.